2008
DOI: 10.2202/1553-3840.1090
|View full text |Cite
|
Sign up to set email alerts
|

Slimpid May Boost Plasma IGF-1 Level and Improve the Quality of Life in Patients with Risk of Developing Metabolic Syndrome

Abstract: Metabolic syndrome (MS) may affect the quality of life (QOL) of patients, and possibly their plasma IGF-1 level. This study is to investigate whether the QOL would be improved and IGF-1 level elevated simultaneously by a Chinese herbal formula, Slimpid (Rhizoma Alismatis, Radix Paeoniae Alba, Semen Cassiae, Pericarpium Arecae, Fructus Crataegi and Astragalus membranaceus). Forty nine subjects with one or more risk factors of MS were divided into Group A (n = 24) and Group B (n = 25) randomly in a double-blinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Results of the present study illustrated that a metabolomics-based analysis of the effects of a multi-component preparation can be used to study potential target processes or novel ingredients. Preparations having their origin in other healthcare systems such as CM have been shown to provide interesting starting points [36] [42] . In a previous study it was found that SUB885C improved insulin sensitivity compared to control in pre-diabetic ApoE*3Leiden mice fed with a high fat diet for 10 weeks [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study illustrated that a metabolomics-based analysis of the effects of a multi-component preparation can be used to study potential target processes or novel ingredients. Preparations having their origin in other healthcare systems such as CM have been shown to provide interesting starting points [36] [42] . In a previous study it was found that SUB885C improved insulin sensitivity compared to control in pre-diabetic ApoE*3Leiden mice fed with a high fat diet for 10 weeks [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The spray‐dried extract containing active ingredients of the medicine was machine‐ground to fine powder form. When used for the preparation of a prescribed decoction, dry powders of individual medicines were mixed in appropriate ratios calculated from the concentration factor and the weight of the raw medicines required for the prescription (Chui et al ., ). Powder concentrates of the chosen CM were obtained from one distributor while the raw medicines were from a different distributor.…”
Section: Methodsmentioning
confidence: 97%
“…For example, Liu et al [31] considered that the Chinese Quality of Life (ChQOL) instrument, a domestic general assessment instrument, reflected the characteristics of Chinese medicine and Chinese culture. Those characteristics specified by the Wong W et al [3] ChQOL instrument (Liu FB et Chui SH et al [4] ChQOL instrument (Liu FB et Liu WH et al [5] ChQOL instrument Wang HY et al [6] ChQOL instrument (Liu FB et Zhang YJ et al [10] Fatigue self-rating scale ( Ji ZY et al [11] Fatigue self-rating scale (Wang TF et al)…”
Section: Application In Basic and Theoretical Researchmentioning
confidence: 99%